El dividendo obligatorio regulado por el artículo 231 de la ley general de sociedades - Ossio Gargurevich, Jorge (2016)
Article 231 of the Peruvian Corporations Act states that, if shareholders that have at least 20% of the voting shares of a company request a distribution of a determined amount of utilities from the previous period, if there are distributable utilities, the company is obligated to distribute them.The author of the present article analyses the convenience of this disposition, from the point of view of the actors involved and taking into account the experience in other countries regarding regulation about the mandatory dividend.Furthermore, the author explains the practical application of article 231, and he inquires and questions the interpretation that has to be given as to allow the disposition to fulfill its objectives.